SUICIDE ATTEMPTS IN PRISON: A FORENSIC ANALYSIS - Muñagorri Sansalvador, Raquel; Peñalver Peña, Marta (Anales de Psicología / Annals of Psychology, 2008)
This article analyzes the causes because the patient J.V., after five years in prison, conducts an attempted suicide by hanging from a door with a string to choke, being cared for and admitted to a hospital. Upon his return to prison is included in the protocol for the prevention of suicides. From this date begins a period marked by a long list of autolytic episodes, which took place about once a month. These episodes were produced in courts wrists and forearms although not with suicidal aims, but as concerned as "to occur more pain and relieve their tension inside", which was sent to the psychiatric service center and put on drug treatment, as well to increase preventive measures of the protocol.To request the Penitentiary Center Madrid IV, ask for exploration psychological valuation of J.V. (25 years) in relation the determination diagnoses of its mental state, the estimation of risk and/or danger and its possibilities of treatament. Provides a detailed analysis of that assessment together with the relevant forensic assessment.